Eksplorasi Pembelajaran Berhitung Melalui Permainan Flashcard Match Up untuk Meningkatkan Kemampuan Berhitung Siswa di kelas Rendah SDN 010096 Karang Anyer Kisaran - Rismayanti Susila; Dalilah Bazliah Ritonga; Ika Purnamasyah; Kiki Fatmalawati Manurung; Nur Habibah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the application of flashcard match-up games in numeracy learning and to describe changes in the numeracy skills of lower-grade students at SDN 010096 Karang Anyer Kisaran based on observations and interviews. This study uses a qualitative approach with a descriptive research type. The research subjects consisted of class teachers and lower-grade students involved in the learning process using flashcard match-up games. Data were collected through observation, interviews, and documentation with instruments in the form of observation guidelines, interview guidelines, and documentation sheets. Data analysis was carried out using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing, while data validity was tested through triangulation of sources and techniques. The results showed that the application of flashcard match-up games showed positive changes in students' numeracy skills, especially in understanding the concepts of simple addition and subtraction. In addition, this game encouraged active student involvement, increased learning motivation, self-confidence, and interaction between students during the learning process. Thus, flashcard match-up games can be an alternative learning media that supports the numeracy learning process in lower grades.